0621 Measures of Function, Work Productivity, and Quality of Life From a Phase 3 Study of Solriamfetol (JZP-110) in Patients with Narcolepsy. (27th April 2018) - Emsellem, H; Thorpy, M J; Lammers, G; Shapiro, C; Mayer, G; Plazzi, G; Chen, D; Li, J; Carter, L P; Ryan, R; Black, J; Dauvilliers, Y
Abstract: Introduction: Solriamfetol is a selective dopamine/norepinephrine reuptake inhibitor with wake-promoting effects. In a phase 3 study, solriamfetol significantly improved wakefulness and decreased excessive sleepiness in adults with narcolepsy. Health-related quality of life (HRQoL) measures were secondary endpoints. Methods: Participants with narcolepsy were randomized to solriamfetol 75mg, 150mg, or 300mg, or placebo for 12 weeks. Secondary measures included the Functional Outcomes of Sleep Questionnaire short version (FOSQ-10), Work Productivity and Activity Impairment questionnaire for Specific Health Problems (WPAI:SHP), and 36-Item Short Form Health Survey version 2 (SF-36v2). Least squares mean (standard error) (LS mean [SE]) change from baseline to week 12 was calculated with significance set at P <0.05. Safety and tolerability were also assessed. Results: Baseline demographics were similar across treatment groups. Solriamfetol 300mg significantly improved the FOSQ-10 score (LS mean [SE]: 300mg, 3.01 [0.42]; placebo, 1.56 [0.40]; P <0.05). Solriamfetol significantly reduced percent overall work impairment on the WPAI at 150mg (LS mean [SE]: 150mg, -19.77 [5.04]; placebo, -4.28 [5.00]; P <0.05) and reduced percent activity impairment at 150 and 300mg (LS mean [SE]: 300mg, -21.27 [3.55]; 150mg, -17.84 [3.35]; placebo, -7.79 [3.42]; P <0.05). Significant improvements in SF-36v2 domains were seen for role physical score (LS mean [SE]: 300mg, 6.46 [1.21]; placebo, 2.38 [1.14]; P <0.05), general health (LS mean [SE]: 75mg, 2.42 [0.84]; placebo, -0.20 [0.81]; P <0.05), and vitality score (LS mean [SE]: 300mg, 4.96 [1.19]; 150mg, 5.83 [1.12]; 75mg, 4.68 [1.15]; placebo, 1.04 [1.12]; P <0.05). The most common treatment-emergent adverse events were headache, nausea, decreased appetite, nasopharyngitis, dry mouth, and anxiety. Conclusion: Solriamfetol improved functioning, and HRQoL, at 300mg, particularly on the vitality (all doses) and role physical domains. HRQoL domains such as emotional and social functioning were not affected. Impairment at work was improved at 150mg, whereas activity impairment outside of work was improved at 150 and 300mg. Safety and tolerability were consistent with previous solriamfetol studies. Support (If Any): Jazz Pharmaceuticals.